DEVELOPMENT OF FUN THINKERS BOOK LEARNING MEDIA IN SOCIAL STUDIES CLASS VII MTS ASHRI SUBJECTS - Miftahul Khotimah; Anindya Fajarini (SOLIDARITY: Journal of Social Studies, 2022)
The limited use of learning media that is less effective causes the learning process to become a problem for students. this makes teaching and learning activities boring. Development of media fun thinkers book to assist the availability of learning media and motivation to participate in teaching and learning activities for social studies subjects. This research purpose: 1) Produce products for the development of social science learning media fun thinkers book for class VII at MTs ASHRI for 2020/2021. 2) Knowing the validity of the product development of social science learning media fun thinkers book class VII at MTs ASHRI for 2020/2021. The method used is R&D, the ASSURE development model. Collecting data using questionnaires and interviews. The research subjects were social studies teachers and 35 seventh-grade students. Data analysis using qualitative and quantitative techniques. The results showed that: (1) material expert validation I with a score of 80.76%